(untitled) - Horstmann, Cay S. (California, 2005)
Book Description Completely revised and up-to-date coverage of Generic programming, restrictions and limitations, type bounds, wilcard types, and generic reflection Swing GUI development, including input validation and other enhancements Exception handling and debugging, including chained exceptions, stack frames, assertions, and logging Streams and files, the new I/O API, memory-mapped files, file locking, and character set encoders/decoders Regular expressions using the powerful java.util.regex package Inner classes, reflection, and dynamic proxies Application packaging and the Preferences API The seventh edition of Core Java- 2, Volume I, covers the fundamentals of the Java 2 Platform, Standard Edition (J2SE-). A no-nonsense tutorial and reliable reference, this book features thoroughly tested real-world examples. The most important language and library features are demonstrated with deliberately simple sample programs, but they aren't fake and they don't cut corners. More importantly, all of the programs have been updated for J2SE 5.0 and should make good starting points for your own code. You won't find any toy examples here. This is a book for programmers who want to write real code to solve real problems.
Keywords: Java (Computer program language)